Al:Cu2O n‑Type SemiconductorsElectrochemical Fabrication of Heterojunction and Homojunction Photovoltaic Devices - Hashimoto, Yui; Mohammad Zain, Mohd Zamzuri; Muraoka, Naoki; Inaba, Rieru; Mohamad, Fariza; Khoo, Pei Loon; Izaki, Masanobu (ACS publication, 2024)
N-type Al:Cu2O semiconductor layers were prepared via cathodic electrodepositions from a copper(II)-lactate complex aqueous solution with added aluminum chloride. Subsequently, the Al:Cu2O/n-ZnO heterojunction and p-Cu2O/ n-Al:Cu2O homojunction photovoltaic devices were constructed by using sequential electrodeposition. The effects of Al impurity were investigated by examining the structural, optical, and semiconductor characteristics of the Cu2O layer using XRD, FE-SEM, XPS, and UV−vis analyses and electrochemical measurements of Mott−Schottky plots. Photovoltaic characteristics were then assessed through current density−voltage curves under AM 1.5G illumination and external quantum efficiency (EQE) for both Cu2O/ZnO heterojunction and p-Cu2O/n-Al:Cu2O homojunction devices. The introduction of Al impurities induced a change in the semiconductor type from intrinsic p-type Cu2O to n-type and decreased carrier concentration while keeping the characteristic cubic lattice. A slight increase in the band gap energy of the Cu2O layers from 2.00 to 2.08 eV was noted with an increase in Al impurity content. The maximum value of the EQE evaluated for the heterojunction photovoltaic devices composed of Cu2O, Al:Cu2O, and n-ZnO semiconductor layers decreased with an increase in Al impurity content. However, the EQE at wavelengths ranging from approximately 630 to 500 nm was enhanced by Al impurity introduction, although the optical absorption characteristics were almost the same in absorption coefficient and dependence on the wavelength, irrespective of the Al content. The enhancement was attributed to an increase in internal quantum efficiency originating from the accelerating dissociation of excitons to free carrier generation for the yellow and green exciton series due to the introduced Al impurities. An EQE of 28% was achieved in the p-Cu2O/n-Al:Cu2O homojunction photovoltaic device, along with enhancements in the EQE values at wavelengths ranging from 630 to 500 nm, showing that both the p-Cu2O and n-Al:Cu2O layers functioned as photovoltaic layers, as evidenced by their external quantum efficiency feature.